Penentuan Prioritas Penanganan Jaringan Jalan Provinsi Metode Analytical Hierarchy Process (Ahp) Berdasarkan Provincial/Kabupaten Roads Management System (Pkrms) - Ilham Halich; Akhmad Suraji; Benny Hidayat (Syntax Literate, 2023)
This PKRMS method combined with the Analytical Hierarrchy Process (AHP) method is expected to get optimal road maintenance results, get the required cost budget and prioritize road handling on strategic roads in West Sumatra province. Road maintenance is carried out to provide road services in accordance with the optimal road service life. West Sumatra Province has 58 provincial roads spread throughout the West Sumatra region, the condition of the road is lightly damaged and heavily damaged. Of the 58 provincial roads, there are 5 strategic sections in the object of research, namely: 2 sections which are transportation access, namely Teluk Bayur Nipah-Purus section (P.098) and Simpang Duku-Ketaping section (P.075) and 3 sections which are agricultural and plantation areas, namely Surantih-Kayo Aro Langgai section (P.086), Panti-Simpang Empat section (P.031) and Abai Sangir-Sungai Dareh section (P.056). The study was conducted by Survey and distributed questionnaires. The survey was conducted by recording inventory data, road condition data, road traffic data which was then processed with PKRMS. The types of handling obtained for the five sections are routine maintenance, periodic maintenance and rehabilitation, the largest budget in the following order: P.056 (Rp. 40,970.5 million), P.086 (Rp. 36,252.5 million), P.031 (Rp. 11,480.5 million), P.075 (Rp. 6,633.8 million), and P.098 (Rp. 5,853.1 million), priority road handling sections are in the following order: P.031, P.056, P.086, P.098, and P.075.